2014
DOI: 10.1039/c4cc01831a
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical aspects and the synthetic scope of the SHi at the sulfur atom. Preparation of enantiopure 3-substituted 2,3-dihydro-1,2-benzoisothiazole 1-oxides and 1,1-dioxides

Abstract: A SHi occurs with complete inversion at the sulfur atom, giving enantiopure 3-substituted benzosulfinamides and benzosulfonamides with preserved carbon configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The absolute configurations were established by single‐crystal X‐ray diffraction analysis of ( S )‐ N ‐cinnamyl‐2,3‐dihydro‐1,2‐benzoisothiazole 1‐oxide ( L1 ) (Figure ). Single‐crystal X‐ray diffraction analysis confirmed that the chiral configuration was completely inverted at the sulfur atom during the intramolecular homolytic substitution, which confirmed the results of Fensterbank and Rodríguez‐Fernández . From the crystal diagram, we can imagine that the two aromatic rings will be like two chiral fences and will produce an excellent chiral surrounding upon its coordination to rhodium or other appropriate metal centers to form a complex.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The absolute configurations were established by single‐crystal X‐ray diffraction analysis of ( S )‐ N ‐cinnamyl‐2,3‐dihydro‐1,2‐benzoisothiazole 1‐oxide ( L1 ) (Figure ). Single‐crystal X‐ray diffraction analysis confirmed that the chiral configuration was completely inverted at the sulfur atom during the intramolecular homolytic substitution, which confirmed the results of Fensterbank and Rodríguez‐Fernández . From the crystal diagram, we can imagine that the two aromatic rings will be like two chiral fences and will produce an excellent chiral surrounding upon its coordination to rhodium or other appropriate metal centers to form a complex.…”
Section: Resultssupporting
confidence: 79%
“…Fortunately, modification of Fensterbank's procedure by using a different base, using toluene in place of benzene, increasing the reaction temperature to 110 °C, and prolonging the injection time of a toluene solution of 2,2′‐azobis(isobutyronitrile) (AIBN) and Bn 3 SnH afforded ( S )‐2,3‐dihydro‐1,2‐benzoisothiazole 1‐oxide with an extremely high enantioselectivity of up to 99 % ee , and it was directly used in the synthesis of the chiral ligands L1 and L2 (Figure and Table ). In addition, chiral 3‐ethyl‐2,3‐dihydro‐1,2‐benzoisothiazole 1‐oxide and 3‐phenyl‐2,3‐dihydro‐1,2‐benzoisothiazole 1‐oxide were prepared according to Rodríguez‐Fernández' procedure, which was reported to have a diastereomeric purity of >98 % dr .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the lower electron‐withdrawing power of the sulfinyl group than that of a Ts group, the addition of trifluoroborane diethyl etherate was necessary for the reaction to proceed smoothly. To the best of our knowledge, this is the first example of a radical addition reaction to N ‐sulfinyl imines . The diastereoselectivity was enhanced when 1i , bearing a more bulky sulfinyl group, was employed .…”
Section: Addition Step: Other Radical Acceptorsmentioning
confidence: 97%
“…In spite of the tremendous amount of reports on the use of the tert ‐butylsulfinyl (tBS) moiety as a stereodirecting group on nitrogen atoms for the asymmetric synthesis of chiral nitrogen‐containing molecules,1 only very few involve control of a radical reaction, and these are limited to addition reactions of radicals to N ‐(tBS)‐imines 2–5. An inherent difficulty associated with such processes is the susceptibility of the sulfur atom of the tBS group to undergo homolytic substitution by radicals, which thus leads to carbon–sulfur bond cleavage 3,6,7. Given the potential of radical chemistry to deliver structurally varied products under mild conditions, finding reactions wherein this process is overridden is a promising prospect that will certainly pave the way for new synthetic applications of tert ‐butanesulfinamides 8.…”
Section: Introductionmentioning
confidence: 99%